Leveraging Climate Finance for Agribusiness SMEs to Scale Up Climate Resilient Agriculture in East Africa: Recommendations for Policy and Practice - Shilomboleni, Helena; Verberk, Rene; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Small and medium-sized enterprises (SMEs) play an important role in supporting sustainable development and increasingly towards building adaptation and resilience in Africa's food and agriculture sectors. However, most agribusiness SMEs operating in small-scale agriculture are in dire need of business finance to help them flourish and climate-proof their value chains as variable weather increasingly threatens their supply sources of raw materials, disrupts their operations, and increases costs of maintenance and materials. Climate-related risk hazards not only increase the risk and unpredictability of SMEs' revenue streams but also reduce private sector investments into the sector even further. Financial institutions such as banks may avoid the risk by not financing agribusiness SMEs or increasing the cost of financing, such as enforcing more stringent collateral requirements or higher interest rates (Csaky et al., 2017).